Peran Efisiensi Anggaran Biaya Produksi Guna Meningkatkan Pendapatan di Yuli Bakery Simo - Latifah Fitriani Dewi; Anita Indah Sayekti; Khoirun Nisa; Siti Marhatus Soleha; Muhammad Aditya Yulianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Focusing on Yuli Bakery, this study aims to examine in depth how production planning budgets and cost effectiveness influence business profitability, particularly in the food and bakery industry sector. This research is based on the assumption that effective production planning can optimize the utilization of available resources, minimize raw material waste, and establish more efficient and structured business operational performance. The study explores the implementation of labor management, raw material management, and production process control oriented toward cost efficiency without reducing product quality, thereby enabling sustainable profitability improvement. The results of the analysis show that Yuli Bakery successfully reduced its cost of goods sold (COGS) by IDR 12,800,000, which directly contributed to an increase in operating profit and gross profit. This cost reduction did not affect overall production volume nor generate additional expenses in other cost components. These findings indicate that even in the absence of significant revenue growth, cost optimization through proper production planning can make a substantial contribution to improving Yuli Bakery’s profitability.